2014
DOI: 10.3389/fimmu.2014.00107
|View full text |Cite
|
Sign up to set email alerts
|

Function and Potentials of M. tuberculosis Epitopes

Abstract: Study of the function of epitopes of Mycobacterium tuberculosis antigens contributed significantly toward better understanding of the immunopathogenesis and to efforts for improving infection and disease control. Characterization of genetically permissively presented immunodominant epitopes has implications for the evolution of the host–parasite relationship, development of immunodiagnostic tests, and subunit prophylactic vaccines. Knowledge of the determinants of cross-sensitization, relevant to other pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 133 publications
0
21
0
Order By: Relevance
“…Their prevalence in the environment results in regular human exposure to different species via different routes, and NTMs can be detected in the respiratory and gastrointestinal tract or on the skin of healthy individuals (12). This environmental exposure can influence resistance to MTB as well as interfere with or enhance the protective immune response to vaccination (14). Several lines of evidence suggest that differences in exposure to NTMs may be an important determinant of the variation in efficacy observed with bCG vaccination (15,16).…”
mentioning
confidence: 99%
“…Their prevalence in the environment results in regular human exposure to different species via different routes, and NTMs can be detected in the respiratory and gastrointestinal tract or on the skin of healthy individuals (12). This environmental exposure can influence resistance to MTB as well as interfere with or enhance the protective immune response to vaccination (14). Several lines of evidence suggest that differences in exposure to NTMs may be an important determinant of the variation in efficacy observed with bCG vaccination (15,16).…”
mentioning
confidence: 99%
“…Firstly, we synthesized 10 MPT63-derived peptides which are potentially restricted by HLA-A Ã 0201 and measured their binding affinity for HLA-A Ã 0201 molecules on the basis of T2 cell line. In vivo immunization experiments revealed that among five high-affinity peptides, two (MPT63 [18][19][20][21][22][23][24][25][26] and MPT6 ) triggered cytotoxic T-cell response whereas the remaining three high-affinity peptides failed to induce IFN-g-secreting T-cell responses. Conversely, three low-affinity peptides (MPT63 [10][11][12][13][14][15][16][17][18][19] , MPT63 [20][21][22][23][24][25][26][27][28] and MPT63 [29][30][31][32][33][34][35][36][37] ) all exhibited immunogenicity in HLA-A Ã 0201 transgenic mice.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 4 and Table 2, all patients responded to one or more immunogenic peptides, the percentage of responding patients varying between 45% and 73%. The percentages of TB patients responding to MPT63 [5][6][7][8][9][10][11][12][13][14] , MPT63 [10][11][12][13][14][15][16][17][18][19] , MPT63 [18][19][20][21][22][23][24][25][26] , MPT63 [20][21][22][23][24][25][26][27][28] and MPT63 [29][30][31][32][33][34][35][36][37] were 63%, 73%, 45%, 60% and 68%, respectively. The combined diagnostic sensitivity of these five immunogenic peptides was 93%.…”
Section: Sensitivity Of High-affinity Peptides In Tuberculosis Diagnosismentioning
confidence: 99%
“…The abundant occurrence of major histocompatibility complex (MHC) class II-permissive epitopes in tubercle bacilli has important implications for the development of both subunit vaccines and diagnostic tests (1,2). Moreover, an evolutionary interpretation has been that selection of Mtb strains carrying protective MHC-permissive epitopes could have extended the survival of infectious individuals and hence was advantageous for the protracted aerosol transmission of the pathogen (1).…”
mentioning
confidence: 99%
“…These endeavors will undoubtedly need to be combined with better knowledge of the functional phenotypes of the respective T cell subsets. Other potential avenues are the construction of fusion proteins with improved vaccine adjuvanticity (7) and the proposed construction of T cell receptor (TCR)-like ligands for immunotherapy (1). Future research may benefit also from advances in computer algorithm based analysis of Mtb epitopes and host cytokine signatures, as well as from reduced costs of DNA and RNA sequencing and synthetic peptide libraries.…”
mentioning
confidence: 99%